Analisis Strategi Pemasaran Yang Tepat Guna Meningkatkan Pangsa Pasar Produk - Agung Setiawan (Universitas Islam Kadiri, 2018)
The results showed that (1) marketing strategy undertaken by PT. Unirama Duta Niaga Kediri is a Stability Strategy (Stability) which emphasizes on not increasing product, market and company functions, more on effort to increase efficiency in order to increase performance and profit. This strategy is relatively low risk. (2) through the analysis of EFAS (External Strategic Factor Analisys Summary) obtained a total score of 3 and through the analysis of IFAS (Internal Strategic Factor Analyys Summary) obtained a total score of 2.95. So that value is inserted in SWOT Analysis showing the position of company PT. Unirama Duta Niaga Kediri in the first quadrant, the appropriate strategy is aggressive strategy or expansion strategy that means the company is in good condition and steady so it is possible to continue to expand, increase growth and achieve progress by maximizing internal and external strength of company in increasing sales volume and excellence (3) Based on the calculation of market share it seems that from year to year experienced an increase, market share achieved by the company, it can be specified that in 2012 market share achieved by the company from the overall sales of the industry amounted to 56.23, In 2013 by 57.91%, 2014 market shareproduction of 59.29%, 2015 market share of 59.67% and 2016 market share of 62.33%.